Utilizing spiritual intelligence and workplace spirituality in creating collective awareness: the U-journey perspective - Baykal, Elif (Frontiers in Psychology, 2024)
Theory U is a process-driven, learning, progress-directed, transformative, and relational approach to social change. This approach is predicated on the idea that spirituality may be used to create communal consciousness through change management. Dealing with spiritual hurdles, practicing meditation, improving sensing, staying in flow, and conceiving are just a few of the special skills needed for success on the U-journey. Spiritual intelligence also includes adaptive problem solving and goal achievement approaches. Theory-U holds that sources other than the outmoded paradigms that gave rise to complex problems are where answers to them must come from. The purpose of this paper is to demonstrate how individuals exposed to workplace spirituality can make better use of their spiritual intelligence. By using spiritual intelligence, people can attain the kind of awareness and engagement required for collective awareness, and this makes sense when we examine awareness awakening processes from the perspective of the U-journey.